Comparative life cycle assessment of different vacuum insulation panel core materials using a cradle to gate approach. (15th January 2021) - Resalati, Shahaboddin; Okoroafor, Tobechi; Henshall, Paul; Simões, Nuno; Gonçalves, Márcio; Alam, Mahmood
Abstract: The global market trend for Vacuum Insulation Panels (VIPs) is projecting a significant increase in their uptake in the construction sector. This is mainly due to the uniquely high-performance properties of the ultra-thin insulation materials. This uptake, however, can potentially be hindered by the VIPs' higher cost and environmental impacts when compared with conventional insulation materials. This paper, for the first time, presents a detailed evaluation of the environmental impact of the most common type of VIPs currently used in different applications with a focus on alternating the core material as the main contributing component to their footprint. Pyrogenic silica, glass fibre, expanded polystyrene, aerogel and a silica/sawdust hybrid core were analysed from cradle to gate. The study, on a comparative basis, demonstrates the sensitivity of the various environmental impact categories to the internal vacuum pressure and the subsequent thermal conductivity values. The results show a lower environmental impact for glass fibre and low density expanded polystyrene compared to the other alternatives. Pyrogenic silica, the most common core material, had the highest environmental impact out of the core materials considered. The higher environmental impacts of pyrogenic silica suggest that measures such as the recycling of the core material alongside the deployment of eco-friendlier manufacturing techniques should be considered if the material is to compete environmentally with the other alternative materials. Graphical abstract: Image 1 Highlights: Environmental impact of different VIP core materials was compared for the first time. Cradle to gate approach has been adopted for the analyses in accordance with EN15804. Sensitivity analyses conducted for internal vacuum pressure and core material EPDs. Pyrogenic silica had the highest environmental impact of the core materials studied. Glass fibre had the lowest environmental impact for vacuum pressures lower than 10Pa.